Decision Making In Mapalus Rumah Culture As A Form Of Women's Empowerment Management - Imran, Treesje; Mambu, Laurens (Pt. Anagata Sembagi Education, 2024)
Women's empowerment in local culture is able to provide opportunities for women in their roles in domestic and public areas which also have an impact on the sustainable family and community economy. This women's empowerment is able to raise the degree of women to stand on an equal footing and partner with men in equality to jointly engage in the role of sustainable family and community economic development. This study aims to identify how the management of women's empowerment in the Mapalus rumah culture through its role in decision making. This research was conducted in Tombatu village, Southeast Minahasa with 10 female informants and analyzed using descriptive qualitative with a phenomenological approach. This research proves that women's empowerment in local culture is able to provide opportunities for women's empowerment in their roles in domestic and public areas which also have an impact on the sustainable family and community economy. In a deep understanding, providing time, space and opportunities for women's empowerment is able to raise the status of women to stand on an equal footing and partner with men in equality to jointly engage in the role of sustainable family and community economic development. This research places its superiority on the ability to make a change in the community paradigm about the important role of women in family economic development through home Mapalus. Thus this research provides a sustainable contribution in efforts to seek and find, build and develop forms of women's empowerment management in various fields.